GENETIC DIVERSITY AMONG SUGARCANE (Saccharum officinarum L.) GENOTYPES AS SHOWN BY RANDOMLY AMPLIFIED POLYMORPHIC DNA (RAPD) - Dwi Hapsoro; Hayane Adeline Warganegara; Setyo Dwi Utomo; Nanik Sriyani; Yusnita Yusnita (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
This experiment was conducted to reveal genetic diversity among 38 genotypes of sugarcane (Saccharum officinarum L.) using RAPD markers. The population consisted of 8 genotypes from Australia, 7 from Africa, 10 from America, and 13 from Asia. Genetic similarity was ranging from 17% to 97% , with the average of 57%. UPGMA dendrograms divided the population into three major groups i.e. group 1, 2, and 3 which consist-ed of 23, 10, and 5 genotypes, respectively. Each major group comprised genotypes of different geographical origins. The dendrogram divided each group into some subgroups. There were 8 subgroups i.e. 4 subgroups in group 1, 2 sub-groups in group 2, and 2 subgroups in group 3. Some genotypes of same geographical origin were clustered into in at least 3 different sub-groups, meaning that they were genetically dis-similar. On the other hand, some other geno-types of different geographical origin were clustered into the same subgroup, meaning that they were genetically similar. This data would help sugarcane breeders to select parents for hybridization in order to maximize heterosis. This could be conducted by selecting parents of dis-similar genotypes.